การศึกษาและพัฒนาศักยภาพด้านการตลาดของผลิตภัณฑ์มีดพร้านาป้อ - พฤฒ ยวนแหล (มหาวิทยาลัยสงขลานครินทร์, 2023)
A study and the development of the marketing potential of the Napo knife product aims 1) to study and analyze consumers' behavior on Napo knife product and others shops 2) to study and analyze the marketing mix factors that affecting the decision to purchase and not purchase the products of Napo knife product community enterprise. 3) to study and analyze the strengths, weaknesses, opportunities, and obstacles of Napo knife product and 4) to find ways to improve the marketing potential of Napo knife product. The population in this study was the customers who purchased and did not purchase the Napo knife product and other products of the Napo knife product community enterprise in 5 provinces namely Trang Province, Krabi Province, Satun Province, Phatthalung Province, and Nakhon Sri Thammarat Province. This research is a survey research. The questionnaire was used as a research tool. Sampling is based on Nonprobability sampling. Quota sampling is required to collect data in Trang, Krabi, Satun, Phatthalung and Nakhon Si Thammarat province. Each province had quota of 80 people, separate into 40 people who buy knives and other products from Napo knife product community enterprise and another 40 people who do not buy knives and other products from Napo knife product community enterprise. The statistics used in the data analysis were percentage, mean and standard deviation. The results of the research show that the development of marketing potential of the Napo knife product are as follows. 1) Napo knife products have many strengths, such as sharpness, persistence, wisdom, and the process of dipping the tip of the naval technician has unique features. Napo knife product community enterprise should focus on these strengths to offer a point of sale to customers especially customers who do not buy the products. Napo knife product community enterprise has to focus on advertising the highlight of the product to the customers. The products should be sold at various OOp distribution centers and participated in product distribution activities at both provincial and national level. Napo knife product community enterprise should encourage young people and interested parties to learn the process of making a knife in order to develop into a skilled workforce in the future. 2) For the price, the price of Napo knife products are lower than those of other brands. Customers can bargain and most customers see that the price is right for the type/size of the product. These are the strength of Napo knife products. They should be used as a strategy to sell products. 3) For the distribution, the Napo knife product community enterprise should always have a ready-to-sell product and should improve the distribution channel to be more diverse. 4) Marketing promotion, the Napo knife product community enterprise should closely look to ensure the seller/staff is courteous and knowledgeable about the product to provide the information to the customers. Furthermore, they should provide product advertising via various media, focusing on selling products online. They should have a business website that has an attractive layout and attracts customers to buy the products.